Leasing as a tool for the development of corporate business Environment (Путеводитель предпринимателя)
In article the essence of financial leasing reveals and possibilities of use of leasing for development of the corporate enterprise environment as conditions of infrastructural maintenance of activity of the enterprises are investigated.